2016
DOI: 10.1002/jcla.22086
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of autoantibodies combined detection for rheumatoid arthritis

Abstract: Anti-BIP and CCP antibodies detected in tandem combination can obtain higher specificity, and have good clinical value for the differential diagnosis of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The same statistic values were recalculated after removing studies. In this meta-analysis, only when the study wrote by Sun et al removed [23], I 2 value of sensitivity goes down from 90.2 to 79.9%, and I 2 value of specificity goes down from 85.9 to 70.4% (Supplementary 2).…”
Section: Sensitivity Analysismentioning
confidence: 81%
See 1 more Smart Citation
“…The same statistic values were recalculated after removing studies. In this meta-analysis, only when the study wrote by Sun et al removed [23], I 2 value of sensitivity goes down from 90.2 to 79.9%, and I 2 value of specificity goes down from 85.9 to 70.4% (Supplementary 2).…”
Section: Sensitivity Analysismentioning
confidence: 81%
“…They finally named it anti-keratin antibody (AKA) [22]. In previous studies, it was found that a specificity of AKA was from 79 to 100% in the diagnosis of RA [23,24], whereas its sensitivity ranged from 20 to 80% [25,26]. Therefore, in order to determine whether AKA can be used as an auxiliary diagnostic serum marker for RA, we carried out this meta-analysis.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In the case of anti-MCV, measurement of this autoantibody demonstrated impressive specificity, positive predictive value and a positive likelihood ratio, as well as significant associations with SDAI response especially with tobacco use, indicative of its potential to act as the preferred RA serodiagnostic procedure in our setting. Although the diagnostic potential of anti-MCV, as well as its role in the immunopathogenesis of RA, are well-described [22,23], as are its associations with other ACPAs, HLA-SE and smoking [24][25][26][27], measurement of this autoantibody in the cohort of RA patients described in the current study appears to be of particular diagnostic value, exceeding the predictive odds ratio of any other ACPA test by four-fold. However, this finding has to be tempered by a consideration of the adjusted cut-off value, warranting further testing with larger cohorts.…”
Section: Discussionmentioning
confidence: 66%
“… 11 12 As the mean age in our study cohort was 59 years, and considering the fact that RF-positivity increases with age leading to a prevalence of more than 10% in healthy elderly over the age of 65 years, this finding is in line with the expectations. 3 4 13 …”
Section: Discussionmentioning
confidence: 99%